Administrative and Legal Counteraction to Illegal Migration: International Experience - BEKTAS, Arman (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The below article researches the system of administrative measures used to combat against illegal migration. Problems on illegal migration have become principal for many countries of the world. At the same time, many countries have been facing them for several decades already. Illegal migration has rather negative impact on the economy, creates the basis for various types of organized crime activity, and in some cases it is a perfect environment for spreading the global terrorism. In a word, it bears the main threat for the existence of both separate states and the whole humankind. Realizing it, many states have developed various protection strategies where administrative measures play an important role. It is the necessity to develop the most efficient administrative measures to protect our country from threats born by the illegal migration that makes us address the most successful examples of the foreign states’ experience, and research possibilities to use it under the national conditions. The work researches laws and regulations that control applying administrative measures in relation to illegal migrants, opinions of researchers on developing efficient counter-measures, and offers variants of using the world experience.